2021
DOI: 10.1007/s00520-021-06253-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic growth after cancer: a scoping review of qualitative research

Abstract: Purpose Interest is growing in post-traumatic growth (PTG) after cancer prompted, in part, by observations of positive associations with health-related quality of life. Qualitative research provides valuable insight into survivors’ experiences. We conducted a scoping review of qualitative evidence on PTG in cancer, determining the number, nature, range and scope of studies, and gaps in the literature. Methods We systematically searched Medline, Scopus, CIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 56 publications
4
46
0
Order By: Relevance
“…e analysis of the mediating effect showed that self-efficacy partially mediated the effect between social support and perception of benefit from illness, with the mediating effect accounting for 35.53% of the total effect, indicating that social support can affect perception of benefit from illness both directly and indirectly through the mediating effect of self-efficacy, which is similar to the results of a related study in China [15]. Self-efficacy reflects the degree to which an individual realizes his or her potential, which can be improved through learning, and higher selfefficacy indicates that acute leukemia caregivers are more confident in their ability to cope with caregiving tasks [16]. When caregivers face frustration and poor mood, the higher their perceived social support, the more they will make full use of the various resources provided by healthcare professionals, family members, and friends, so that their internal self-efficacy will increase, they will take the initiative to learn about disease treatment, master caregiving skills, improve their caregiving adaptability, reduce anxiety and depression, and other negative emotions, and, at the same time, enhance the positive experience brought about by caregiving.…”
Section: E Mediating Role Of Self-efficacy Between Caregiver's Social...supporting
confidence: 78%
See 1 more Smart Citation
“…e analysis of the mediating effect showed that self-efficacy partially mediated the effect between social support and perception of benefit from illness, with the mediating effect accounting for 35.53% of the total effect, indicating that social support can affect perception of benefit from illness both directly and indirectly through the mediating effect of self-efficacy, which is similar to the results of a related study in China [15]. Self-efficacy reflects the degree to which an individual realizes his or her potential, which can be improved through learning, and higher selfefficacy indicates that acute leukemia caregivers are more confident in their ability to cope with caregiving tasks [16]. When caregivers face frustration and poor mood, the higher their perceived social support, the more they will make full use of the various resources provided by healthcare professionals, family members, and friends, so that their internal self-efficacy will increase, they will take the initiative to learn about disease treatment, master caregiving skills, improve their caregiving adaptability, reduce anxiety and depression, and other negative emotions, and, at the same time, enhance the positive experience brought about by caregiving.…”
Section: E Mediating Role Of Self-efficacy Between Caregiver's Social...supporting
confidence: 78%
“…With the continuous improvement of medical technology and improvement, the 5-year survival rate of acute leukemia patients is as high as 68%, in which the careful care of caregivers is one of the important reasons for their extended survival time. Caregivers can have a negative impact on their physical and mental health due to the heavy caregiving tasks and psychological stress [16,17]. Related studies confirmed that the negative psychological state of caregivers decreases the quality of care, which in turn reduces the quality of life of patients with acute leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, allostatic overload in women with BC should be better investigated [35][36][37][38][39] as the framework for efficient health management in survivorship favouring emotional resilience. As highlighted in some research protocols, women with BC experience negative emotions and transform that into personal growth [40][41][42][43][44]; the improvement of mental health into the AL framework is becoming an emerging topic. According to the AL framework, and confirming the emotional regulation model in cancer experience [45], our study confirmed the positive frame of mind of women with BC after primary oncological treatments, evidencing a strong ability to manage the negative emotions through an emotional regulation process producing adaptive responses, as well as mental flexibility in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Numerous studies have reported resilience and post-traumatic growth among patients with cancer and their caregivers. [17][18][19][20][21] The experience of cancer can also allow individuals to reflect on their lives and re-evaluate their choices, resulting in more meaning and satisfaction in life. 22 Furthermore, robust evidence supports that patients undergoing cancer treatment lean into their spirituality and re-engage in activities that enhance meaning and overall quality of life during and after cancer treatment.…”
Section: Introductionmentioning
confidence: 99%